(3TQM eSfO GdTGaYis - (3CHhSYjO SfLQ YHO Gddg GdfGUQi GdLGhdis; (3GdGeGe GdTGaYj , CHh YHO Gddg,J (B204 (3g` s
(3ChdgG (B:s
(3CNHQfG GdTGaYj QVj Gddg Yfg CNHQfG edc GHf YeQ Cf QShd Gddg Udi Gddg Ydjg hSde bGd (B:( (3dGjHjY HYVce HjY HYV (B) (3CNQLg ef GdLRA GdKGfi ef ENJdGa GdMOjK s
(3BNQgG (B:s
(3hbO QDi eQGQkG Ydi HYV GdCHhGH hGbakG ai GdTeS dbO WGd bjGec ai GdTeS abGd djWhd bYOi ai GdXd hGddg GYde s
(3GdfSNI HgG MhGTs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B26 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B32s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1683s
Keywords: (3GdMOjK h GdeUWdMs